Observation of strong two-electron--one-photon transitions in few-electron ions - Togawa, Moto; Kühn, Steffen; Shah, C.; Amaro, P.; Steinbrügge, R.; Stierhof, J.; Hell, N.; Rosner, Michael; Fujii, K.; Bissinger, M.; Ballhausen, R.; Hoesch, M.; et al. (Physical review, 2020)
We resonantly excite the K series of O5+ and O6+ up to principal quantum number n=11 with monochromatic x rays, producing K-shell holes, and observe their relaxation by soft-x-ray emission. Some photoabsorption resonances of O5+ reveal strong two-electron-one-photon (TEOP) transitions. We find that for the [(1s2s)15p3/2]3/2;1/2 states, TEOP relaxation is by far stronger than the radiative decay and competes with the usually much faster Auger decay path. This enhanced TEOP decay arises from a strong correlation with the near-degenerate upper states [(1s2p3/2)14s]3/2;1/2 of a Li-like satellite blend of the He-like Kα transition. Even in three-electron systems, TEOP transitions can play a dominant role, and the present results should guide further research on the ubiquitous and abundant many-electron ions where electronic energy degeneracies are far more common and configuration mixing is stronger.
Gesehen am 07.01.2021